The 100 Top-Cited Systematic Reviews/Meta-Analyses on Diabetic Research - Yi Yang; Yao Ma; Lingmin Chen; Yuqi Liu; Yonggang Zhang (Journal of Diabetes Research)
Objective. The objective of this study was to analyze the 100 top-cited systematic reviews/meta-analyses on diabetic research. Methods. The Science Citation Index Expanded database was searched to identify top-cited studies on diabetic research up to March 4th, 2020. Studies were analyzed using the following characteristics: citation number, publication year, country and institution of origin, authorship, topics, and journals. Results. The 100 top-cited diabetic systematic reviews/meta-analyses were published in 43 different journals, with Diabetes Care having the highest numbers (n=17), followed by The Journal of the American Medical Association (n=14) and Lancet (n=9). The majority of studies are published in the 2000s. The number of citations ranged from 2197 to 301. The highest number of contributions was from the USA, followed by England and Australia. The leading institution was Harvard University. The hot topic was a risk factor (n=33), followed by comorbidity (n=27). Conclusions. The 100 top-cited systematic reviews/meta-analyses on diabetic research identify impactful authors, journals, institutes, and countries. It will also provide the most important references to evidence-based medicine in diabetes and serve as a guide to the features of a citable paper in this field.